1 Analysis of dietary intake and biliary tract cancer risk in 638,860 Chinese and European adults in three cohort studies - Valerie Gunchick; Wei Zheng (Journal of Clinical and Translational Science, 2023)
OBJECTIVES/GOALS: Biliary tract cancer is an uncommon, aggressive malignancy. Incidence varies geographically and is highest in East Asia and South America and lowest in Western countries. Previous dietary risk evaluations have primarily been case-control studies. We evaluated associations of dietary intakes with BTC risk in three cohort studies in two countries. METHODS/STUDY POPULATION: We evaluated 638,860 adults in China and the United Kingdom enrolled in the Shanghai Women’s Health Study (SWHS), Shanghai Men’s Health Study (SMHS), or UK Biobank (UKB). Dietary intake information was obtained from study participants at baseline using food frequency questionnaires previously validated for these studies. Dietary intakes of major food groups and macronutrients were divided into low, middle, and high intake tertiles. Cox regression was used to estimate hazard ratios and 95% CIs for biliary tract cancer risk associated with major food groups in all three cohorts and macronutrients in the SWHS and SMHS. Participants were excluded if, at enrollment, they had a history of cancer, CHD, stroke, a total daily Kcal count below 500 or exceeding 3500, or developed cancer or died within one year after enrollment. RESULTS/ANTICIPATED RESULTS: The analyzed cohort includes 558,372 participants: 66,945 SWHS, 55,750 SMHS, and 435,677 UKB participants with median enrollment ages of 49, 52, and 57 years old and median follow-up times of 18.1, 12.3, and 10.3 years, respectively. The SWHS observed 205 eligible BTC cases, SMHS 97, and UKB 366. SWHS and SMHS participants were combined for dietary evaluation and the highest tertile of fruit intake showed an inverse association with biliary tract cancer risk when compared to the lowest tertile: HR 0.74 (95% CI, 0.55-0.99); p-trend 0.044. In UKB, the highest tertile of fish intake was associated with a reduced risk when compared to the lowest tertile: HR 0.76 (95% CI, 0.59-0.98); p-trend 0.034. DISCUSSION/SIGNIFICANCE: High dietary fruit intake was associated with a reduced risk of biliary tract cancer only in SWHS and SMHS. High fish intake was associated with a reduced risk of biliary tract cancer only in UKB. Our findings reflect geographic-based BTC risk variation which we will further explore in our next model accounting for population-specific risk factors.